Neutral scatterers dominate carrier transport in CVD graphene with ionic impurities. (15th September 2020) - Chen, Szu-Hua; Nguyen, Yen; Chen, Ting-Wei; Yen, Zhi-Long; Hofmann, Mario; Hsieh, Ya-Ping
Abstract: The carrier conduction in 2D materials is more sensitive to surface-bound disorder than bulk materials and is thought to limit their achievable performance in electronic devices. To date, charged impurity scattering is considered the main source of interaction between ionic adsorbates and carriers in 2D materials. We here observe a previously unknown source of carrier scattering in graphene upon interaction with ionic impurities. Different from charged impurity scattering, these "neutral scatterers" do not depend on carrier concentration and yield a sixfold mobility variation at similar doping. Comparison of different ionic residue from various metal etchants reveals a universal mechanism that controls the carrier mean free path. Raman spectroscopy suggests that inhomogeneous charge distribution is the source of neutral scatterers and we extract an optical fingerprint for their presence. The charge heterogeneity thus acts as an additional degree of freedom in graphene's carrier transport and its consideration can explain the transition from ambipolar to unipolar charge transport in graphene. Our results not only provide new insight into the carrier transport of 2D materials in the presence of disorder and provide guidelines for enhancing the performance of graphene devices but also enable novel device concepts in graphene. Graphical abstract: Image 1